Hemorragia subaracnoidea aneurismática: descripción de 2 años en la Unidad de Paciente Crítico del Instituto de Neurocirugía – Dr. Alfonso Asenjo - Castaño T., Héctor Fabio; Amudio L., Cristián; Agudelo M., Ángela María; Gómez S., Robinson (Revista Hospital Clínico Universidad de Chile, 2016)
Backgrond: Aneurysmal subarachnoid haemorrhage has an incidence of 7 per 100,000 patients / year and only a third of patients end up without severe sequelae or death. Arm: We reviewed the clinical records of patients with diagnosis of subarachnoid hemorrhage during two years of the neurosurgery institute Dr. Alfonso Asenjo (Chile). Material and Methods: An observational, retrospective study including 231 patients with a diagnosis of aneurysmal subarachnoid hemorrhage, 33 (12.5%) were excluded per stay less than 72 hours or not admitted to the unit, corresponding to bleeding from other causes or not found Information, the database was reviewed during January 2015 to December 2016 of the statistical department of the Institute of Neurosurgery. Results: A total of 231 patients, 165 (71%) women and 66 (29%) men, were analyzed. It was found that hypertension with 120 (51.9%) and smoking with 89 (38.5%) cases were the most frequent risk factors. Endovascular treatment was performed on 100 patients (43%) and 128 (57%) were operated and 3 were not operated. Vasospasm was present in 130 cases (56.3%). Mortality was present in 15 patients died, so the mortality was 6.5%. Conclusions: There was no statistical significance between the type of therapy resolution pathway (endovascular/surgical) with P = 0.6530 with a a 0.05, but because there was a limited access to endovascular therapy at the neurosurgery institute at daytime hours from Monday to Friday versus the neurosurgical availability 24x7, being discordant with the statistical results of equal amount of treatment between the two pathways.